2014
DOI: 10.1556/crc.2013.0069
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × tillage interaction in a recurrent selection program in wheat

Abstract: The objective of this study was to test if the response to 10 cycles of a recurrent selection program conducted under conventional tillage and rain fed conditions was the same when contrasted, for several traits, under conventional and non-tillage practices. During two season (2011 and 2012) the 44 S-derived families (four/C 0 to C 10 populations) were evaluated under conventional and non-tillage systems in two fields next to each other. Days to anthesis, plant height, grain, and biomass yield and 1000-grain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Moreover, Sadras and Connor (1991) established a simple and consistent relationship between harvest index and the fraction of water transpired after anthesis. Monneveux et al (2004 a-b), showed that higher yields in wheat are accompanied by increased straw ash content; similarly, the improvement for grain yield under CT, found by Maich and Di Rienzo (2014), working on the materials of the same selection program on which this paper is based, are also related with an increase in straw ash content. Not being the water stored in the soil a limiting factor, in the NT soil management (D) Figure 1.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Moreover, Sadras and Connor (1991) established a simple and consistent relationship between harvest index and the fraction of water transpired after anthesis. Monneveux et al (2004 a-b), showed that higher yields in wheat are accompanied by increased straw ash content; similarly, the improvement for grain yield under CT, found by Maich and Di Rienzo (2014), working on the materials of the same selection program on which this paper is based, are also related with an increase in straw ash content. Not being the water stored in the soil a limiting factor, in the NT soil management (D) Figure 1.…”
Section: Discussionmentioning
confidence: 74%
“…A significance level of 5% was used to interpret results. Statistical calculations were performed by InfoStat statistical software (Di Rienzo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maich and Di Rienzo (2014) show a significant genetic progress for GY when the wheat crop was cultivated in CT, which did not occur when grown in NT. However, a significant advance was observed for grain yield per spike, a grain yield per unit area component, when the genetic gain was measured in NT.…”
Section: Discussionmentioning
confidence: 94%
“…Various approaches have been used. For example, progress has been evaluated from the differences between historic check cultivars and the mean yield of highest yielding lines, cultivars from different eras in common environments (Giunta et al 2007), or materials derived from successive cycles of recurrent selection (RS) (Maich and Di Rienzo 2014).…”
Section: Introductionmentioning
confidence: 99%